Ekspansi Aplikasi Aqua Breeding dengan Penambahan Fitur Inventarisasi untuk Penentuan Harga Dasar Produk Perikanan Berbasis Android - Alfatih, Akbar Maulana; Muhammad Eka Suryana; Med Irzal (J-KOMA : Jurnal Ilmu Komputer dan Aplikasi, 2023)
Freshwater fisheries cultivation is one of the fisheries sources in Indonesia. In cultivation, it is important to record inventory indicators such as fish feed, fish supplements, pond assets, pond electricity, and fish seed, which are useful in determining fish selling prices. This research aims to expand the application of Aqua Breeding by adding inventory features for recording inventory usage and determining minimum fair fish prices. Data for this study were derived from discussions with freshwater fish cultivators from JFT (J Farm Technology) and literature studies involving relevant research journals. These discussions resulted in user requirements that guided the creation of a web service backend and its implementation on a mobile frontend. The system development method employed was Scrum with five sprints, utilizing Flask with Python for the backend and Flutter with Dart for the frontend technologies. The final outcome of this research is a web service in the form of a REST API with documentation, integrated into an Android-based application, validated through unit testing and User Acceptance Testing (UAT).